Evaluating methods to explore antibiotic use on smallholding pig farms in peri-urban Kenya - Scott, C.; Bor, Nicholas; Reyher, K.K.; Tasker, A.J.; Buller, H.; Korir, Max; Muloi, Dishon M.; Bueno, I.; Thomas, Lian F. (Frontiers Media, 2025)
Background: Understanding patterns and practices of antibiotic use (ABU) in livestock is crucial to make informed recommendations for improved antibiotic stewardship and to measure the impact of interventions aimed at reducing inappropriate ABU. In the absence of a unified tool to determine ABU at the farm level, we aimed to enhance the understanding of methodological approaches used to explore ABU by evaluating the strengths and limitations of four different methods on smallholding pig farms in a peri-urban area of Nairobi, Kenya.